Parameter optimization for automated behavior assessment: plug-and-play or trial-and-error? - Luyten, Laura; Schroyens, Natalie; Hermans, Dirk; Beckers, Tom (Frontiers in Behavioral Neuroscience, 2014)
Behavioral neuroscience is relying more and more on automated behavior assessment, which is often more time-efficient and objective than manual scoring by a human observer. However, parameter adjustment and calibration are a trial-and-error process that requires careful fine-tuning in order to obtain reliable software scores in each context configuration. In this paper, we will pinpoint some caveats regarding the choice of parameters, and give an overview of our own and other researchers' experience with widely used behavioral assessment software. We conclude that, although each researcher should weigh the pros and cons of relying on software vs. manual scoring, we should be aware of possible divergence between both scores, which might be especially relevant when dealing with subtle behavioral effects, like for example in generalization or genetic research.